A Review of Emerging Dual‐Ion Batteries: Fundamentals and Recent Advances. (3rd March 2021) - Zhang, Luojiang; Wang, Haitao; Zhang, Xiaoming; Tang, Yongbing
Abstract: Dual‐ion batteries (DIBs), based on the working mechanism involving the storage of cations and anions separately in the anode and cathode during the charging/discharging process, are of great interest beyond lithium‐ion batteries (LIBs) in high‐efficiency energy storage due to the merits of high working voltage, material availability, as well as low cost and excellent safety. Despite the progress achieved, the practical applications of DIBs are still hindered by negative issues, such as limited capacity and cyclic stability, which triggers the development of suitable electrode materials with highly reversible capacities, and corresponding electrolytes with high oxidative stability as well as sufficient reaction kinetics of active ions. Herein, in this article, a systematic and comprehensive review of fundamentals and recent advances in current DIBs with subcategories of cathode materials, anode materials, and electrolytes are presented. In particular, their energy storage mechanisms, as well as their respective features, are dissected. Furthermore, some strategies and perspectives are proposed for facilitating the further development of DIBs in the future. Abstract : The electrochemical performance of the dual‐ion battery is closely concerned with suitable electrode materials and corresponding electrolytes, which further determines the practical applications in energy storage. This review summarizes the recent advances and challenges of cathode materials, anode materials, and electrolytes in current dual‐ion batteries, and proposes perspectives for further study in the future.